2018
DOI: 10.1002/ags3.12221
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term clinical outcomes of laparoscopic gastrectomy for remnant gastric cancer: A single‐institution experience and systematic review of the literature

Abstract: Aim Application of laparoscopic approaches for the treatment of remnant gastric cancers (RGC) is still controversial. Therefore, in the present study, the safety and effectiveness of laparoscopic gastrectomy (LG) for RGC was investigated. Methods A total of 27 patients who underwent gastrectomy for RGC from June 2008 to September 2017 were enrolled in this study. A comprehensive review of the literature on LG for RGC published before December 2017 using the PubMed database was carried out. Results Laparoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Many surgeons have successfully applied LCTG, and this technique is considered the preferred treatment option (Table 5) [24][25][26][27][28][29][30][31][32][33]. As shown in Table 6, our results are consistent with those of comparative studies [14][15][16][17][18][19][20][21]. The patients in the LCTG group had smaller tumor size, lower numbers of metastatic lymph nodes, and lower pathological stages than patients in the OCTG group; however, the clinical stage distribution, dissection, and retrieved lymph nodes showed no signi cant differences between the groups.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Many surgeons have successfully applied LCTG, and this technique is considered the preferred treatment option (Table 5) [24][25][26][27][28][29][30][31][32][33]. As shown in Table 6, our results are consistent with those of comparative studies [14][15][16][17][18][19][20][21]. The patients in the LCTG group had smaller tumor size, lower numbers of metastatic lymph nodes, and lower pathological stages than patients in the OCTG group; however, the clinical stage distribution, dissection, and retrieved lymph nodes showed no signi cant differences between the groups.…”
Section: Discussionsupporting
confidence: 85%
“…The patients in the LCTG group had smaller tumor size, lower numbers of metastatic lymph nodes, and lower pathological stages than patients in the OCTG group; however, the clinical stage distribution, dissection, and retrieved lymph nodes showed no signi cant differences between the groups. Additionally, the number of retrieved lymph nodes was equal to that reported in other studies (Table 6) [14][15][16][17][18][19][20][21]. The OCTG group had a higher number of recurrences and deaths than the LCTG group, because the OCTG group had more advanced cases, leading to a worse 5-year overall survival rate than the LCTG group.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Six studies reported that the conversion rate to open gastrectomy was 5.6-47.1%; the other 15 studies reported no cases of conversion to open gastrectomy. In all studies, the mean operation time ranged from 197 to 487 min, the mean blood loss was up to 425 g, the mean number of retrieved lymph nodes ranged from 7 to 26 and the mean duration of postoperative hospital stay (18)(19)(20)(21)(22)(23)(24). Among these 8 studies, 6 studies showed that LTG was associated with less blood loss, 4 studies showed that LTG was associated with a longer operation time, and 1 study showed that LTG was associated with a greater number of retrieved lymph nodes and shorter postoperative hospital stay in comparison to the OTG group.…”
Section: Resultsmentioning
confidence: 99%
“…All studies comparing the operating time between OG and LG reported that LG required more time than OG, even though the difference was not statistically significant in five out of the ten studies[64-66,68,69]. However, LG was associated with lower intraoperative blood loss than OG in six of the ten studies[60,61,65,66,68,69]. The number of resected lymph nodes was reported in all non-RCTs and case studies.…”
Section: Laparoscopic Gastrectomy For Remnant Gastric Cancermentioning
confidence: 99%